Information Aggregation and Policy - Weiss, Laurence (Review of Economic Studies, 1982)
The function of monetary policy to alter the informational content of money price signals is examined in a model where traders can observe an economy wide financial signal and a local commodity price. Under a passive policy, money demand disturbances, which are not directly observable, are shown to be confused with real productivity shocks and thereby preclude prices from fully reflecting all information. Even when the policy authority has no informational advantage, prospective money growth feedback rules can “improve” the structure of available information.